К вопросу создания и исследования эффективности работы автономных систем энергообеспечения на основе возобновляемых источников энергии - Воронцов, Я. С.; Антипов, Е. А. (Енергетика і автоматика, 2017)
UDC 621.1.016:620.97(075.8) TO THE QUESTION OF ESTABLISHMENT AND RESEARCH OF EFFICIENCY OF WORK OF AUTONOMOUS ENERGY SUPPLY SYSTEMS BASED ON RENEWABLE ENERGY SOURCES J. VORONTSOV, I. ANTYPOV Introduction. In recent years, the construction of individual residential houses in suburban areas where there is no centralized heat and gas supply is widely spread in Ukraine. In these conditions, the use of autonomous energy supply systems based on renewable energy sources (RES) is promising. The use of such systems will provide significant savings for both natural gas and other traditional energy sources. Analysis of recent researches and publications. Given the wide variety of renewable energy equipment (wind generators, photovoltaic cells, solar collectors, batteries, etc.), it is possible to develop a variety of energy systems of different combinations of primary energy sources. However, the low density of the renewable energy flow and the inability to regulate the regimes of its supply do not allow us to focus the development of energy exclusively on RES. Currently, the most eco-nomically effective options are the joint application of traditional energy resources (TER), RES and energy accumulators as part of a single system for obtaining thermal and electrical energy. Purpose. Тo justify the feasibility of creating autonomous systems of power supply for a community consumer using renewable energy sources. Methods. Having analyzed the general provisions of transformation and use of renewable energy sources we will schematically show the processes of transformation, accumulation and use of renewable energy sources. For this purpose, in the path of the energy flow-solar, wind, geothermal, etc., spontaneously flowing from such a source into the atmosphere of the Earth or to the surface of its land or water body, a transducer (transformer) of energy is set up, in which capture, transformation, and, if necessary and the concentration of primary renewable energy. Further, it is converted into energy of some other kind (thermal, electrical, mechanical, etc.), it is sent to the consumer, and if at the moment it is not necessary, then in the energy battery, from where it is fed to the engineering equipment for example, heating, hot water supply, ventilation, etc. Different methods of management are used to reconcile energy sources with consumers. From the foregoing it follows that in power systems with RES and in small AEC based on RES, three control methods based on the discharge of surplus energy, the accumulation of energy and the change in load can be used. These methods can be implemented in various ways for the entire power system or its parts and are illustrated by such examples. Summarizing the results of a number of scientific developments and practical experiments of both domestic and foreign researchers, an AEС with RES was proposed based on the use of solar radiation energy and / or an electrical network with the possibility of accumulating its excess in accumulators of electrical and thermal energy of an improved design. Results. The results of the research show that the share of alternative energy in energy consumption for given parameters of the model is about 31 % for electric and 66 % for thermal energy, respectively. At the same time, the efficiency of covering the load of consumers due to the use of accumulated electric energy is between 95...100 %, and the thermal load - 84...89 %. Discussion. Consideration of the general principles of transformation and use of renewable energy sources and their comparison with traditional energy sources allows us to state the following: 1. The use of renewable energy in power systems and energy complexes is always determined by specific natural and climatic conditions and the needs of a specific region in energy for various sectors of the national economy. 2. The use of renewable energy does not lead to additional thermal pollution of the environment, while using renewable energy, there are practically no other harmful effects on the environment, which makes them highly valuable, practically environmentally friendly sources of energy. 3. At present, in small autonomous energy complexes, the options for the joint use of TER and RES are most economically effective. With the increase in prices for fuel and energy resources, tightening of environmental requirements for energy sources and improvement of renewable energy conversion systems, their share in energy balances will increase, which will lead to the evolution of these complexes and, ultimately, to transform into small AECs with renewable energy sources. 4. As a result of the conducted studies, the expediency of using electric and thermal energy accumulators in the AEC with the use of solar energy is justified. In particular, the following is established: - part of the alternative energy in energy consumption for given parameters of the model is about 31 % for electric and 66 % for thermal energy, respectively; - the efficiency of covering the load of consumers due to the use of accumulated electric energy is in the range 95...100 %, and thermal - 84...89 %.